How the true colors™ typology is related to adolescents choosing not to smoke cigarettes: an exploratory study - Richmond, Mary Frances (Kansas State University, 2014)
This qualitative research study was conducted in order to understand more about the phenomenon of adolescent cigarette smoking and to contribute to the body of knowledge on youth substance abuse prevention. The exploratory study incorporated the personality types associated with True Colors, Inc. (2008), as a tool to use when gathering information from non-smoking adolescents and parents. Adolescent-parent dyads were interviewed about how personality characteristics influenced several factors regarding the adolescents’ choice to not smoke cigarettes. The participants indicated that they were comfortable with the True Colors model for identifying their personality types. Furthermore, the participants tended to provide information that reflected their personality. The “gold” personalities exhibited a strong sense of right and wrong, and it was important for them to be responsible, follow rules and respect authority. The adolescents identified as having “orange” personalities tended to put themselves at the center of conversations and reported that they made many of their own decisions. They were also spontaneous and witty. Personalities that were “blue” types demonstrated the most compassion and empathy. They valued relationships and they did not want to disappoint others when making decisions. The fourth color was the “green” personality. These individuals were visionaries, and were analytical and logical with their responses. They valued knowledge and were apt to get their information from books and television when making decisions. Implications for research include that, rather than studying why adolescents do smoke cigarettes, it may be wise to also study why adolescents choose to not smoke cigarettes in order to more fully understand the phenomenon. The study also provided implications for practitioners regarding adolescent cigarette smoking prevention programs. Because the current study found differences in how the personality types of adolescents received information, youth prevention programs should utilize a variety of strategies to address the unique differences in adolescent personalities in order to be most effective.
Keywords: Education; Health education; Home economics education; Education, General (0515); Health Education (0680); Home Economics Education (0278)